Implementation of School-Based Management in Indonesia - Vernez, Georges (RAND Corporation, 2012)
This study provides a quantitative and qualitative status report on the implementation of school-based management (SBM) in Indonesia, identifies factors associated with the successful practices of SBM, and assesses SBM effects on student achievement eight years after inception. They found that the implementation so far has produced limited success and provide recommendations to strengthen the nation's SBM practices.